RECONSTRUCTION OF LOCAL GOVERNMENT AUTHORITY IN GOVERNMENT EMPLOYEE MANAGEMENT WITH EMPLOYMENT AGREEMENTS (PPPK) BASED ON THE MERIT SYSTEM AFTER THE LAW – LAW NUMBER 20 OF 2023 CONCERNING THE STATE CIVIL SERVICE: A STUDY OF STATE ADMINISTRATIVE LAW - Nia Avenasari, (Proceeding International Conference on Social Sciences, 2026)
After the enactment of Law Number 20 of 2023 concerning State Civil Apparatus, there have been fundamental changes to the authority of local governments in the management of government employees with work agreements, with a focus on the implementation of the Merit System. This law requires the reconstruction of local government authority to align personnel management policies with the principles of a more rigorous and transparent merit system. The purpose of this study is to identify the reconstruction of local government authority in each PPPK management cycle and to evaluate the implications of these changes on the principles of regional autonomy and public accountability. This study uses a normative legal research method, with a statute approach and a conceptual approach. Primary legal materials, namely Law Number 20 of 2023, and secondary legal materials are analyzed qualitatively to find clarity of norms and consistency of regulations. The Civil Service Law strengthens the central role of the Central Government in determining the Norms, Standards, Procedures, and Criteria (NSPK) for PPPK management, which implies centralized supervision to ensure the uniform application of the Merit System nationwide. This reconstruction of authority shifts local governments from managers with broad discretion to designated technical operational implementers who must fully comply with the meritocracy standards set by the central government, including planning, recruitment, talent development, and performance appraisal. In terms of state administrative law, this reaffirms the principle of legality in regional personnel management and increases the accountability of local governments to avoid abuse of authority (detournement de pouvoir) in order to realize professional civil service management that is free from patronage practices.